2019
DOI: 10.1021/jacs.9b09110
|View full text |Cite
|
Sign up to set email alerts
|

ReB6: A Metallaboron Analog of Metallabenzenes

Abstract: Metallabenzenes are a class of molecules in which a CH unit in benzene is replaced by a functionalized transition-metal atom. While all-boron analogues of aromatic and antiaromatic hydrocarbons are well-known, there have not been any metallaboron analogs. We have produced and investigated two metal-doped boron clusters, ReB6 – and AlB6 –, using high-resolution photoelectron imaging and quantum chemical calculations. Vibrationally resolved photoelectron spectra have been obtained and compared with the theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 73 publications
0
36
0
Order By: Relevance
“…The structures and relative energies of other low-lying isomers within 1 eV of the global minimum are given in Figure S1. The ground state of MnB 6 – consists of a B-centered six-membered ring with Mn being on the periphery, similar to the structure of ReB 6 – . While ReB 6 – is closed shell, MnB 6 – is found to have a high spin state ( 5 A 2 ) with an electron configuration of 1a 1 2 1b 2 2 2a 1 2 2b 2 2 1b 1 2 3a 1 2 1a 2 2 3b 2 2 4a 1 2 4b 2 2 - 5a 1 2 6a 1 1 7a 1 1 2b 1 1 5b 2 1 .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The structures and relative energies of other low-lying isomers within 1 eV of the global minimum are given in Figure S1. The ground state of MnB 6 – consists of a B-centered six-membered ring with Mn being on the periphery, similar to the structure of ReB 6 – . While ReB 6 – is closed shell, MnB 6 – is found to have a high spin state ( 5 A 2 ) with an electron configuration of 1a 1 2 1b 2 2 2a 1 2 2b 2 2 1b 1 2 3a 1 2 1a 2 2 3b 2 2 4a 1 2 4b 2 2 - 5a 1 2 6a 1 1 7a 1 1 2b 1 1 5b 2 1 .…”
Section: Resultsmentioning
confidence: 78%
“…We report an investigation of a 3d transition-metal metallaboron cluster, MnB 6 – , produced by laser vaporization of a mixed Mn/B target. The selection of Mn was inspired by the recent synthesis of manganacycles and the ReB 6 – metallaboron analog of 5d metallabenezenes . High-resolution photoelectron imaging (PEI) in conjunction with computational chemistry has shown that MnB 6 – has a planar structure with the Mn atom on the periphery of the cluster, similar to that of ReB 6 – .…”
Section: Introductionmentioning
confidence: 99%
“…Various aromaticity criteria have been proposed theoretically since aromaticity is not a directly measurable quantity. Herein, different criteria demonstrated as effective in probing aromaticity of metal clusters, [27][28][29][30][31][32][33][34][35][36] including magnetic [nucleus-independent chemical shift (NICS) and magnetic susceptibility anisotropy Δχ] and electronic [multicenter indices (MCI) and localized orbital locator (LOL)] indices were calculated to examine their aromaticity in both the T 0 and S 1 states. The explanations about other criteria that are not indicated here are listed in Supporting Information Note 1.…”
Section: Resultsmentioning
confidence: 99%
“…According to high-resolution photoelectron imaging and quantum chemical calculations, it is also the GM of B 6 Re − and B 6 Mn − . 91,92 The study on B 6 Al − reported a detailed AdNDP analysis, which shows four peripheral B–B bonds and two B–Al bonds as 2c-2e σ-bonds and three 7c-2e σ- and two 7c-2e π-bonds. 89 The preference for the hexagonal arrangement with a B in the center and the dopant at the periphery is maintained even in the experimentally observed B 6 Ta − .…”
Section: Introductionmentioning
confidence: 99%